The Impact Of Zakat On Improving Of The Communitys Economy - Anisah, Ariyun (Al-Kharaj: Journal of Islamic Economic and Business, 2024)
Theoritically, zakat has important role in economic, the multiplier effect of zakat can imcrease peoples income. Consumtive zakat can give long term multiplier effect to economy, so do productive zakat. The distribution of zakat in National Zakat Agency South Solok regency is divided into five programs, namely: Prosper South Solok, Smart South Solok, Healty South Solok, Piety South Solok, and Care South Solok. However, in its application the portion of productive zakat (Prosper South Solok) is less than consumtive zakat. This research is aimed to discover the impact of zakat on improving communitys economy in South Solok regency marked with increasing of income. The subject of research is people who accepted productive zakat fund from National Zakat Agency South Solok Regency. Sampling is done using purposive sampling technique consisted of 72 respondents. Data collection technique is conducted through interview, questionnaire, and documentacy. Data analysis technique utilized simple linear regression. Research revealed zakat has significant influence on improvement of communitys economy in South Solok regency